2005
DOI: 10.1172/jci23621
|View full text |Cite
|
Sign up to set email alerts
|

Sources of fatty acids stored in liver and secreted via lipoproteins in patients with nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by the accumulation of excess liver triacylglycerol (TAG), inflammation, and liver damage. The goal of the present study was to directly quantify the biological sources of hepatic and plasma lipoprotein TAG in NAFLD. Patients (5 male and 4 female; 44 ± 10 years of age) scheduled for a medically indicated liver biopsy were infused with and orally fed stable isotopes for 4 days to label and track serum nonesterified fatty acids (NEFAs), dietary fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,668
3
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,920 publications
(1,819 citation statements)
references
References 48 publications
44
1,668
3
14
Order By: Relevance
“…Recently published data from patients with severe insulin resistance due to lipodystrophy or the loss of function mutations in the insulin receptor gene itself (INSR) suggest that metabolic dyslipidaemia is due in part to increased hepatic lipogenesis driven by hyperinsulinaemia. This also appears to be true in obese patients with fatty liver (Donnelly et al 2005) and in diabetic offspring (Petersen et al 2007). After binding to the insulin receptor, insulin action is mediated by a complex, incompletely understood branching signalling network.…”
Section: Pathogenesis Of Hepatic Steatosismentioning
confidence: 94%
“…Recently published data from patients with severe insulin resistance due to lipodystrophy or the loss of function mutations in the insulin receptor gene itself (INSR) suggest that metabolic dyslipidaemia is due in part to increased hepatic lipogenesis driven by hyperinsulinaemia. This also appears to be true in obese patients with fatty liver (Donnelly et al 2005) and in diabetic offspring (Petersen et al 2007). After binding to the insulin receptor, insulin action is mediated by a complex, incompletely understood branching signalling network.…”
Section: Pathogenesis Of Hepatic Steatosismentioning
confidence: 94%
“…Serum FFA levels are elevated in all of these disorders [16] . It was reported that the main source for TG in hepatocytes was derived from circulating FFAs in NAFLD [17] . Although we did not analyze serum fatty acid levels in our study, down-regulation of miR-99a in NASH was concordant with this evidence.…”
Section: ) and Further Confirmed By Sam Test (Q < 5%)mentioning
confidence: 99%
“…In this context, TG accumulation > 55 mg/g measured by MRI or by histological examination is its key diagnostic feature [12,13] . Fatty acids (FA) account for approximately 60% of TG in the liver of NAFLD patients, while approximately 15% originate from dietary fat [14] . De novo production is responsible for the rest 25% [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids (FA) account for approximately 60% of TG in the liver of NAFLD patients, while approximately 15% originate from dietary fat [14] . De novo production is responsible for the rest 25% [14] . Insulin resistance plays a key role in the pathogenesis of NAFLD [2,15,16] .…”
Section: Introductionmentioning
confidence: 99%